Ultrasonic production of nano-emulsions for bioactive delivery in drug and food applications. (2018) - Leong, Thomas Seak Hou; Manickam, Sivakumar; Martin, Gregory J. O; Li, Wu; Ashokkumar, Muthupandian
No abstract available